Masalah-Masalah Demokrasi: Diskursus Hak Mayoritas dan Minoritas - franky P Roring, M. Si (Universitas Bung Karno, 2022)
AbstractThis article discusses the limitations of democracy. Democracy substantively recognizes the existence of minority rights and the rights of the majority. The establishment of majority rights can give rise to the tyranny of the majority which is harmful to the interests of the minority. However, minorities can also be in power and control the politics of a country, so the majority vote is also ignored. Majority and minority discourse becomes important in the relationship between politics and power.Keywords: Majority, Minority, Democracy. Abstrak Artikel ini membahas mengenai masalah keterbatasan demokrasi. Demokrasi secara substansif mengakui eksistensi hak minoritas dan hak mayoritas. Pengutamaan hak mayoritas dapat memunculkan tirani mayoritas yang berbahaya bagi kepentingan minoritas. Walaupun demikian, minoritas juga dapat kelompok yang berkuasa dan mengontrol politik suatu negara, sehingga suara mayoritas juga terabaikan. Diskursus mayoritas dan minoritas menjadi hal penting dalam relasi antara politik dan kekuasaanKata Kunci : Mayoritas, Minoritas, Demokrasi.